33 The diagnostic yield of screening first-degree relatives in sudden arrhythmic death syndrome. (5th October 2017) - Toh, T; Coyne, C; Stewart, K; Muir, A; McCall, D
Abstract : Introduction: While the commonest cause of sudden death remains coronary artery atherosclerosis, when detailed post mortem examination fails to find any abnormality in an individual with no history of cardiac disease, the term sudden arrhythmic death syndrome (SADS) is applied. Conditions that may result in SADS are often familial and screening of first-degree relatives according to a protocol of clinical assessment and cardiac investigation is frequently undertaken. We aimed to assess the diagnostic yield of this approach in individuals referred to the Belfast Trust Inherited Cardiac Conditions Clinic because of SADS in a first degree relative. Methods: Retrospective analysis of clinic databases between January 2012 and December 2015 was undertaken. Where SADS was listed as reason for attendance, it was confirmed the patient was a first degree relative of the deceased and that post-mortem including toxicological analysis had failed to reveal a cause of death. The outcome and conclusions of screening in each individual were then assessed using medical records and cardiac investigation databases. Results: We identified 55 incidents of SADS with referral of first-degree relatives for screening. Data were available on 97 individuals, at least one from each family. All those screened had a standard resting 12 lead ECG, 96% had a transthoracic echocardiogram, 89% had an exercise stress test, 88% had ambulatory ECG monitoring, 69% had an ajmaline challenge. Based on screening of first-degree relatives, a diagnosis was made in 6 (10.9%) families and 8 (8.2%) individuals. In four families, one individual was diagnosed with Brugada Syndrome based on a Type 1 ECG response to ajmaline. In another family, 1 individual had QT prolongation on repeated ECGs without apparent secondary cause or genetic explanation on standard testing. In the remaining family, 3 members were shown to have QT prolongation on 12 lead ECGs and each carried the same mutation in KCNH2, consistent with long QT syndrome, type 2. Discussion: These findings suggest that in SADS cases, the diagnostic yield from a strategy based solely on screening of first-degree relatives is low. Our protocols are consistent with other centres. The highest yield investigations appear to be resting 12 lead ECG and ajmaline challenge. It is important that each individual attends screening under such difficult circumstances is made aware that the process may well provide reassurance but is unlikely to yield a definitive cause for their loved ones death. In the majority of SADS cases, precise diagnosis remains elusive. This provides an opportunity for improvement through continued development of molecular autopsy panels linked to large bioinfomatic databases.